2021
DOI: 10.3390/nano11061514
|View full text |Cite
|
Sign up to set email alerts
|

Co-Encapsulation of Methylene Blue and PARP-Inhibitor into Poly(Lactic-Co-Glycolic Acid) Nanoparticles for Enhanced PDT of Cancer

Abstract: The development of resistance against photodamage triggered by photodynamic therapy (PDT) is ascribed mainly to the cellular redox defenses and repair. If the tumor tissue is not promptly eliminated by the first few PDT sessions, PDT-resistance can be favored, challenging the efficacy of the treatment. Although the mechanism of PDT resistance is still unclear, in vitro assays have evidenced that it can be developed through the PARP damage-repair signaling pathway. Therefore, inhibition of poly(adenosine diphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Furthermore, it was discovered that these TB@PLGA NPs have an excellent tumor suppression effect in vivo [138]. For increased PDT of malignancies, PLGA NPs are employed for the regulated release of PS MB with a PARP inhibitor, veliparib in a very low concentration [139]. These VMB NPs showed no toxicity in the dark but when they were irradiated with visible light they showed significant toxicity against B16F10-Nex2 cells [139].…”
Section: Gelatinmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was discovered that these TB@PLGA NPs have an excellent tumor suppression effect in vivo [138]. For increased PDT of malignancies, PLGA NPs are employed for the regulated release of PS MB with a PARP inhibitor, veliparib in a very low concentration [139]. These VMB NPs showed no toxicity in the dark but when they were irradiated with visible light they showed significant toxicity against B16F10-Nex2 cells [139].…”
Section: Gelatinmentioning
confidence: 99%
“…For increased PDT of malignancies, PLGA NPs are employed for the regulated release of PS MB with a PARP inhibitor, veliparib in a very low concentration [139]. These VMB NPs showed no toxicity in the dark but when they were irradiated with visible light they showed significant toxicity against B16F10-Nex2 cells [139]. PEG is a polymer that is used to conjugate polyester NPs and micelles for drug entrapment in both hydrophobic and hydrophilic environments.…”
Section: Gelatinmentioning
confidence: 99%
“…Another study that assesses the effectiveness of PDT using MB-loaded NPs is mentioned in [ 176 ]. However, in contrast to the previously presented study, [ 176 ] examines not only the effect of MB alone but also its combined effect with veliparib, which is a poly(adenosine diphosphate (ADP)-ribose) polymerase (PARP) inhibitor. The PARP damage-repair signalling pathway might be involved in the PDT resistance mechanism; thus, inhibiting PARP might improve the PDT effect.…”
Section: Non-porphyrin Photosensitizersmentioning
confidence: 99%
“…The photoactivity was found to increase by this encapsulation approach. Overall, the results demonstrated that the cytotoxicity was enhanced by using PDT therapy combined with PARP inhibitor [ 108 ].…”
Section: Nanoformulations For Delivery Of Parp Inhibitors To Cancer Cellsmentioning
confidence: 99%